Management of Hepatitis B: A Longitudinal National Survey – Impact of the Canadian Hepatitis B Consensus Guidelines - Paul Marotta; Kurt Lucas (Canadian Journal of Gastroenterology)
BACKGROUND: The Canadian Association for the Study of the Liver, and The Association of Medical Microbiology and Infectious Diseases Canada, jointly developed the Canadian Chronic Hepatitis B (HBV) Consensus Guidelines to assist practitioners involved in the management of this complex disease. These guidelines were published in The Canadian Journal of Gastroenterology in June 2007 and distributed to all Canadian gastroenterologists and hepatologists.